State of archaeological research in Cagayan Valley, Northern Luzon, Philippines - Ronquillo, Wilfredo P. (2000)
The significance of the Cagayan Valley as an archaeological area was first reported by H. Otley Beyer in 1947, when the presence of fossilized remains of elephants were found during a mining prospecting activity. In the early 1970s, the Cagayan Valley Archaeological Project was launched by the National Museum, resulting in the discovery and recording of over 100 sites in the anticlines and synclines at Cagayan, Kalinga and Apayao Provinces. Fossilized remains of elephants and rhinoceros were encountered eroding from the surface of the Pleistocene Bed called the Awidon Mesa Foundation. Directly associated with the large animal bones were numerous stone cobbles and flake tools assumed to be of the same age as the fossils and the Pleistocene geological deposits. Due to the lack of widespread in situ sites, geologists from the Iowa State University were invited to resolve the geological problem facing the archaeologists in 1975. In the hiatus, National Museum archaeologists started an archaeological survey of the Peñablanca Limestone Formation about 15 kilometers west of Tuguegarao, the capital of Cagayan Province, hoping to encounter stone artifacts. Indeed, the over 100 caves, rock shelters and open-air sites recorded during a two-month survey in 1976-1977 indicate the rich archaeological potential of the limestone formation as a habitation and burial area of prehistoric man in the Philippines. Subsequent archaeological excavations in a number of caves and rock shelters in the area showed sites from the Stone Age period to sites with earthenware pottery indicative of interaction between hunter-gatherers and settled people from pottery-making villages. The dates of the use of the caves by hunter-gatherers were ca. 3000 B.C., and later. Recently the focus of archaeological work was in the vicinities of Lal-lo, Cagayan or, more precisely, areas west and east of Cagayan River where shell midden have been noted to be ubiquitous. Large deposits of shell midden have been identified along the riverbanks, inland from the banks, and on elevated areas away from the riverbanks. These are indicative of different populations of settled groups of people exploiting the resources of both the river and existing forest as shown by the tons of shells and numerous animal bones and teeth. The objective of the Cagayan Valley Archaeological Project remains the understanding of the long evolution of man and his society in the Northern Philippines through systematic archaeological research work entailing a multi-disciplinary approach.
Includes bibliographical references (pages 31-34).
Keywords: Archaeology -- Research -- Philippines -- Cagayan Valley; Archaeology -- Philippines -- Cagayan Valley